The role of the governor of the Islamic state in protecting human rights from the perspective of Quran and Sunnah - Ahmed S.A., Al-Qodsi; Sharifah Norshah Bani, Syed Bidin (2019)
The governor of the Islamic State plays an active role in the protection of human rights from violations. However, in recent years, the Arab and Islamic arena has witnessed tensions and disobedience between the governor and the folk. This has created a state of hostility and hatred among the members of the same society, resulting in wars and destruction. To the contempt of the governor in the care of human rights, and failure to carry out his duties stipulated by the texts of the Quran and Sunnah. The purpose of this research is to clarify the role of the Governor in the Islamic State and its role in the maintenance of human rights in light of the provisions of the Holy Quran and Sunnah. The research used the analytical approach to analysis of the issues, to reach the real results for a clear understanding of the subject. The research found the following results: The Governor must be responsible for the care of human rights in the Islamic State, the importance of the Governor's role in guaranteeing human rights, and the need for the Governor to treat the parish with mercy and tenderness and for the Governor to fulfill his duties to human rights in five areas: Scholars and their advice to him in the care and protection of human rights, and the governor should monitor the actions of the governors on the care of human rights, and the need to raise the governor of violations of human rights, and the importance of accountability and isolation of the aggressors and defaulters in the preservation of human rights, At the hands of the Governor and urged him to take care of and preserve human rights.